Grand Research Challenges for Sustainable Industrial Biotechnology. Issue 10 (October 2019) - Straathof, Adrie J.J.; Wahl, S. Aljoscha; Benjamin, Kirsten R.; Takors, Ralf; Wierckx, Nick; Noorman, Henk J.
Abstract : Future manufacturing will focus on new, improved products as well as on new and enhanced production methods. Recent biotechnological and scientific advances, such as CRISPR/Cas and various omic technologies, pave the way to exciting novel biotechnological research, development, and commercialization of new sustainable products. Rigorous mathematical descriptions of microbial cells and consortia thereof will enable deeper biological understanding and lead to powerful in silico cellular models. Biological engineering, namely model-based design together with synthetic biology, will accelerate the construction of robust and high-performing microorganisms. Using these organisms, and ambitions towards zero-concepts with respect to emissions and excess resources in bioprocess engineering, industrial biotechnology is expected to become highly integrated into sustainable generations of technology systems. Highlights: Recent biotechnological and scientific advances are paving the way to exciting novel biotechnological research, development, and commercialization of new sustainable products. Rigorous mathematical descriptions of microbial cells and consortia thereof will enable deeper biological understanding and lead to powerful in silico cellular models. Biological engineering will accelerate the construction of robust and high-performing microorganisms. Using these organisms and 'zero-concepts' in bioprocess engineering, industrial biotechnology will become highly integrated into sustainable generations of technology systems.